SYSTEMATIC LITERATURE REVIEW: AN ANALYSIS OF LEARNING MODELS TO IMPROVE STUDENTS' MATHEMATICAL LITERACY - Dea Erlita; Isnaini Rosyida; Adi Nur Cahyono (Universitas Sembilanbelas November Kolaka, 2026)
The low level of Indonesian students' mathematical literacy remains a major challenge in education, as reflected in various national and international assessment results such as PISA. One effort that can be made to improve students' mathematical literacy is through the implementation of appropriate learning models. This study aims to analyze learning models that have been proven effective in improving students' mathematical literacy skills. The method used is Systematic Literature Review with six stages: formulating research questions, establishing selection criteria, developing a search strategy, study selection, quality assessment, and synthesis of results. Literature search was conducted using the Publish or Perish application based on Google Scholar with a range of years 2016–2026. From the initial 200 articles, 17 articles met the inclusion criteria and passed the Quality Assessment stage. The results show that the most widely used learning models that are proven effective in improving students' mathematical literacy include: Problem Based Learning, Project Based Learning, Discovery Learning, Realistic Mathematics Education, Learning Cycle 7E, inquiry model with scaffolding, Group Investigation, Collaborative Learning, and Accelerated Learning Cycle. These models are effective because they encourage active student involvement, contextualization of real problems, and development of critical thinking skills.